2010
DOI: 10.1103/physrevc.81.044909
|View full text |Cite
|
Sign up to set email alerts
|

Hot and dense hadronic matter in an effective mean-field approach

Abstract: We investigate the equation of state of hadronic matter at finite values of baryon density and temperature reachable in high-energy heavy-ion collisions. The analysis is performed by requiring the Gibbs conditions on the global conservation of baryon number, electric charge fraction, and zero net strangeness. We consider an effective relativistic mean-field model with the inclusion of isobars, hyperons, and the lightest pseudoscalar and vector meson degrees of freedom. In this context, we study the influence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 94 publications
1
75
0
Order By: Relevance
“…Thus, by considering the deconfinement transition at finite density as a first-order one, a mixed phase can be formed, which is typically described using the two separate equations of state: one for the hadronic phase, and one for the quark phase. To describe the mixed phase, we apply the Gibbs formalism to systems with more than one conserved charge [54,55], requiring that baryon number, electric charge and strangeness number are preserved. The main result is that, at variance with the so-called Maxwell construction, the pressure in the mixed phase is not strictly constant and therefore, for instance, the nuclear incompressibility does not vanish.…”
Section: Mixed Hadron-quark-gluon Phasementioning
confidence: 99%
“…Thus, by considering the deconfinement transition at finite density as a first-order one, a mixed phase can be formed, which is typically described using the two separate equations of state: one for the hadronic phase, and one for the quark phase. To describe the mixed phase, we apply the Gibbs formalism to systems with more than one conserved charge [54,55], requiring that baryon number, electric charge and strangeness number are preserved. The main result is that, at variance with the so-called Maxwell construction, the pressure in the mixed phase is not strictly constant and therefore, for instance, the nuclear incompressibility does not vanish.…”
Section: Mixed Hadron-quark-gluon Phasementioning
confidence: 99%
“…Particularly, turning off the ∆-ρ coupling which contributes the potential part of the symmetry energy (retaining thus kinetic symmetry energy only), the ρ crit ∆ − is about 3ρ 0 [16]. Interest has been renewed with recent studies using different symmetry energies and/or assumptions about the baryon-meson coupling constants which have found that the ρ crit ∆ − can be as low as ρ 0 and the inclusion of the ∆(1232) has significant effects on both the composition and structure of neutron stars [19][20][21][22][23][24]. These studies generally use some individual sets of model parameters leading to macroscopic properties of ANM at saturation density consistent with most if not all of the existing experimental constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we are going to study a EOS at finite temperature and density by means of a relativistic mean-field model with the inclusion ∆(1232)-isobars [4][5][6] and by requiring the Gibbs conditions on the global conservation of baryon number and net electric charge. In regime of finite values of density and temperature, a state of high density resonance matter may be formed and the ∆(1232)-isobar degrees of freedom are expected to play a central role in relativistic heavy ion collisions and in the physics of compact stars [7,8] Alternating Gradient Synchrotron (AGS) to RHIC [9,10].…”
Section: Introductionmentioning
confidence: 99%